BIOSORBEN BUAH JABON PUTIH (Anthocephalus cadamba Miq.) UNTUK MENJERAP ION LOGAM MERKURI (II) - Faradilla Milenia; T. Abu Hanifah; Sofia Anita; Mufidah Salsabila; Anastasia Kinzky Zipora Nainggolan (Pelantar Press, 2024)
This aims of this study to determine the efficiency and adsorption capacity of the biosorbent in absorbing mercury (II), determine the adsorption kinetics and isotherm model and the biosorbent regeneration ability of white jabon fruit. The optimization of the biosorbent powder was carried out on the parameters of pH, contact time and adsorbate concentration. The biosorbent is regenerated by desorption using an HCl desorption agent. Jabon fruit biosorbent powder was made through the drying process of Jabon fruit that has been cut and washed and then ground using a mortar and pestle. The results of the physical and chemical characteristics in this study showed a water content value of 8.09%, ash content of 1.32%, iodine adsorption capacity of 753.5812 mg/g and methylene blue adsorption capacity of 24.8632 mg/g. The results of the biosorption test showed that the optimum conditions for the biosorbent powder were pH 6 with an efficiency of 99.728% and a capacity of 4.7855 mg/g, a contact time of 40 minutes with an efficiency of 99.493% and a capacity of 4.7747 mg/g, at an initial concentration of 80 mgL-1 with an efficiency of 99,912. % and the capacity was 3,5761 mg/g. Based on the FTIR results, the functional groups were C-H aliphatic, C-H aromatic, C=O, C-O and N-H. Based on the results of BET analysis, biosorbent powder had a surface area before adsorption of 3.53039 m2/g, after adsorption I 0 m2/g and after regeneration II 0.17056 m2/g. Based on the SEM-EDS results, it was found that the jabon fruit biosorbent powder had elements of O, C, Na, N, Cl, K, Hg and had an uneven texture. However, because it was in powder form, the distance between the particles looked very tight and has a small grain size. So the surface texture looked very smooth. In this study, the percentage of regeneration was 98.36%. The adsorption kinetics of this study follows the second-order Pseudo equation where the equation was y = 0.2097x - 0.0075 with R2 = 1 and K= 5.86339 gmg-1min-1, assuming a chemical adsorption process which includes intervalence forces or electron exchange between the adsorbent and adsorbate and the adsorption isotherm model follows the Langmuir equation with the equation y= 0.019x + 0.0153 with R2 = 0.9665 It is assumed that the active site on the surface of the adsorbent is homogeneous.